STUDY TECHNOLOGY IN THE VILLAGE RUGEMUK TRAWL DISTRICT PANTAI LABU SUB REGENCY DELI SERDANG NORTH SUMATRA - Indra Sanjaya Purba; Arthur Brown; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in April 2015 in the waters of the East Coast of Sumatra precisely in the Village District of Pantai Labu Rugemuk Deli Serdang, North Sumatra. The study aims to analyze aspects of pengeoperasian trawl and trawl fisheries business development opportunities in the village Rugemuk. The study was conducted using descriptive method of study is based on observation, interview and documentation. The study was focused on aspects Pengeoperasian and feasibility analysis. To determine management strategies based trawling in the waters of the coast of pumpkin used Feasibility analysis effort.Trawling is a fishing tool (API) which is the dominant practice in the fishing village of regemuk. APIs are also many other types of fishing practiced in the village regemuk is tuguk and Kelong. Trawl fishing gear is the type of bag-shaped nets catcher is equipped with a pair (2 pieces) board net mouth opening (otter boards).Investment of Rp. 60.2 million, the production cost of Rp. 282 924 000, gross income amounted to Rp. 336 480 000. the value of Benefit Cost Ratio of 1.10. Financial rate of retrun 55% and a payback period of capital value by 1 year 8 months.Keywords: trawling, Technology, Management, Pantai Labu.